PENGELOLAAN PENDIDIKAN INKLUSIF DI SMPN 23 BANJARMASIN - Muhammad Ahyat; Isny Lellya (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Inclusive education is an education delivery system that provides opportunities for all students who have disabilities and have potential intelligence and/or special talents to participate in education or learning in one educational environment together with students in general. National Education System Law no. 20 of 2003, Article 5 paragraphs 1 and 2, states that every citizen has the same right to quality education and citizens with physical, emotional, mental, intellectual and social disabilities have the right to receive special education. Children with special needs receive a good education to develop their abilities and potential and receive educational services tailored to their needs. This type of research is field research, the researcher comes directly to the research site and makes observations regarding the problems that exist in the management of inclusive education at SMPN 23 Banjarmasin. This research approach is descriptive qualitative, collecting data from a natural setting with the intention of interpreting a phenomenon that occurs. Planning for new student admissions at SMPN 23 Banjarmasin begins with the formation of a new student admissions committee led by the general chairman, principal, chief executive, secretary, treasurer and other members. Organizing was carried out in the formation of a committee to determine the requirements for new students, then four stages were created, namely, recruitment, selection of new students, orientation of new students, and placement of students. Special supervising teachers (GPK) play a very important role in looking after children with special needs (ABK), the implementation of learning there, subject teachers also work together with GPK teachers, SMPN 23 Banjarmasin using the 2013 curriculum. Supervision at SMPN 23 Banjarmasin is recorded, the The homeroom teacher takes notes about his students, and the recording for ABK is carried out by the GPK. Reporting uses report cards to determine student progress.